Research of Agricultural Sector Support Process in Russia’s Economy - KUZNETSOV, Nikolai Ivanovich; UKOLOVA, Nadezhda Viktorovna; MONAKHOV, Sergey Vladimirovich; SHIKHANOVA, Juliya Anatolyevna (Journal of Advanced Research in Law and Economics; Vol 7 No 8 (2016): JARLE Volume VII, Issue 8(22), Winter 2016, 2017)
Characteristics of the process to support the agricultural sector of the Russian economy are being analyzed in the article on the basis of a comprehensive scientific study. The theoretical and methodological aspects of the support process of the agrarian sector of the economy, based on in-depth analysis of scientific papers of Russian scientists investigating support and development of this sector are being researched. Existing normative legal documents, programs in the agricultural sector at the federal and regional levels are being analyzed. Level of support for the agricultural sector revealed the relationship between the amount of support and the level of production is being carefully studied. Macroeconomic data describing the current level of agricultural production in Russia, the dynamics of the volume of imported food, the trends of the main branches of the Russian agricultural sector, considering regional experience in the development of the agrarian sector in Saratov region are being presented. The article emphasizes the need to improve the process of supporting the agricultural sector of the Russian economy, due to increased volume and the need to improve its efficiency.